Cyclophilin A is required for an early step in the life cycle of human immunodeficiency virus type 1 before the initiation of reverse transcription. - Braaten, D (1996)
Cyclophilin A (CyPA) is incorporated into human immunodeficiency virus type 1 (HIV-1) virions via contact with the Gag polyprotein. Genetic or pharmacologic disruption of CyPA incorporation causes a quantitative reduction in virion infectivity with no discernible effects on virion assembly or on endogenous reverse transcriptase activity. Instead, the reduction of virion-associated CyPA is accompanied by a parallel, quantitative decrease in the initiation of viral DNA synthesis after infection of T cells. The infectivity of CyPA-deficient virions is not restored by pseudotyping with Env of amphotropic murine leukemia virus, demonstrating that CyPA is not required for the HIV-1-Env-CD4 interaction. These results indicate that CyPA is required for an early step in the HIV-1 life cycle following receptor binding and membrane fusion but preceding reverse transcription. CyPA is the first cellular protein other than the cell surface receptor shown to be required for an early event in the life cycle of a retrovirus.